Routledge handbook of tourism cities - Morrison, Alastair M., 1949-; Coca-Stefaniak, Andres (Routledge, 2021)
This section combines academic scholarship with real-life practice and case studies from cities. Part III discusses product and technology developments for tourism cities, examining their supply and impact on different travellers, from open-air markets to creative waterfronts, from social media to smart cities. The final Part offers examples of how urban tourism is developing in different parts of the world and how worldwide tourism cities are adapting to the challenges ahead. It also explores emerging forms of specialist tourism, including geology and ecology-based tourism, socialist heritage and post-communist destination tourism. This handbook fills a notable gap by offering a critical and detailed understanding of the diverse elements of the tourist experience today. It contains useful suggestions for practitioners, as well as examples for theoretical frameworks to students in the fields of urban tourism and tourism cities.-The handbook will be of interest to scholars and students working in urban tourism, heritage studies, human geography, urban studies and urban planning, sociology, psychology and business studies.